Post-anaesthesia pulmonary complications after use of muscle relaxants (POPULAR): a multicentre, prospective observational study. Issue 2 (February 2019) - Kirmeier, Eva; Eriksson, Lars I; Lewald, Heidrun; Jonsson Fagerlund, Malin; Hoeft, Andreas; Hollmann, Markus; Meistelman, Claude; Hunter, Jennifer M; Ulm, Kurt; Blobner, Manfred; ,
Summary: Background: Results from retrospective studies suggest that use of neuromuscular blocking agents during general anaesthesia might be linked to postoperative pulmonary complications. We therefore aimed to assess whether the use of neuromuscular blocking agents is associated with postoperative pulmonary complications. Methods: We did a multicentre, prospective observational cohort study. Patients were recruited from 211 hospitals in 28 European countries. We included patients (aged ≥18 years) who received general anaesthesia for any in-hospital procedure except cardiac surgery. Patient characteristics, surgical and anaesthetic details, and chart review at discharge were prospectively collected over 2 weeks. Additionally, each patient underwent postoperative physical examination within 3 days of surgery to check for adverse pulmonary events. The study outcome was the incidence of postoperative pulmonary complications from the end of surgery up to postoperative day 28. Logistic regression analyses were adjusted for surgical factors and patients' preoperative physical status, providing adjusted odds ratios (ORadj ) and adjusted absolute risk reduction (ARRadj ). This study is registered withClinicalTrials.gov, numberNCT01865513 . Findings: Between June 16, 2014, and April 29, 2015, data from 22 803 patients were collected. The use of neuromuscular blocking agents was associated with an increased incidence of postoperative pulmonary complications in patients who had undergone general anaesthesia (1658 [7·6%] of 21 694); ORadj 1·86, 95% CI 1·53–2·26; ARRadj −4·4%, 95% CI −5·5 to −3·2). Only 2·3% of high-risk surgical patients and those with adverse respiratory profiles were anaesthetised without neuromuscular blocking agents. The use of neuromuscular monitoring (ORadj 1·31, 95% CI 1·15–1·49; ARRadj −2·6%, 95% CI −3·9 to −1·4) and the administration of reversal agents (1·23, 1·07–1·41; −1·9%, −3·2 to −0·7) were not associated with a decreased risk of postoperative pulmonary complications. Neither the choice of sugammadex instead of neostigmine for reversal (ORadj 1·03, 95% CI 0·85–1·25; ARRadj −0·3%, 95% CI −2·4 to 1·5) nor extubation at a train-of-four ratio of 0·9 or more (1·03, 0·82–1·31; −0·4%, −3·5 to 2·2) was associated with better pulmonary outcomes. Interpretation: We showed that the use of neuromuscular blocking drugs in general anaesthesia is associated with an increased risk of postoperative pulmonary complications. Anaesthetists must balance the potential benefits of neuromuscular blockade against the increased risk of postoperative pulmonary complications. Funding: European Society of Anaesthesiology.